Control Methods on Three-phase Power Converters in Photovoltaic Systems - Othmane Salama; Abdelmoumen Tabyaoui; Mohamed Benchagra (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
In this paper, a three-phase load connected to a NPC three-level inverter is presented. To generate gate signals for the multilevel inverter, two commands are developed and compared: the phase disposition pulse width modulation (PDPWM) and the space vector pulse width modulation (SVPWM). DC supply is provided by photovoltaic cells. Boost converter controls the power transfer from photovoltaic generator. Due to nonlinear I-V characteristics of photovoltaic cells, a maximum power point tracking algorithm is adopted to maximize the output power, the nonlinear controller (sliding mode) is developed and simulated. To verify the effectivnesse of the introdueced controller, it is compared with the fuzzy logic controller. Matlab-simulink is used for simulation, analysis and interpretation the results of these controllers.